The effects of fertilization treatments and cropping systems on long-term dynamics and spectroscopic characteristics of dissolved organic matter in paddy soil. Issue 6 (2nd November 2019) - Wu, Huiqiao; Kida, Morimaru; Domoto, Akiko; Hara, Masayuki; Ashida, Hitoshi; Suzuki, Takeshi; Fujitake, Nobuhide
ABSTRACT: We investigated a series of long-term soil samples (1976–2015) collected from a paddy field that underwent a conversion of cropping systems from double cropping to single cropping in 1991, with consistently different fertilization treatments. The fertilization treatments include (i) chemical fertilizer, (ii) chemical fertilizer + rice straw, (iii) chemical fertilizer + cattle manure compost, and (iv) chemical fertilizer + rice straw + fused phosphate + calcium silicate. We extracted dissolved organic matter (DOM) from the soil samples and analyzed it for the concentration of humic substances as well as for optical properties using ultraviolet-visible and excitation-emission matrix (EEM) spectroscopy. Different fertilization treatments did not significantly (P > 0.05) affect DOM and humic substance concentrations, while the soil total carbon (TC) content and DOM concentration consistently increased in the double cropping system and decreased in the single cropping system. The DOM/TC ratio, which is an indicator of the proportion of the labile fraction in TC pool, also showed a similar pattern. These results indicate that cropping systems had a larger effect on DOM concentration than the fertilization treatments. Five fluorescent components identified by parallel factor analysis of EEMs (three humic-like and two protein-like components) showed significant differences in the relative abundances under the different fertilization treatments. The manure compost application resulted in a higher tyrosine-like component relative abundance than the other chemical fertilizer applications. Overall, fertilization affected the DOM composition, while the cropping systems impacted both the concentration and spectroscopic property of paddy soil DOM.